Harmonising Nurses’ Roles to Clinical Environment: A Synergy to Theory-Based Nursing Practice - Jafaru, Yahaya (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Introduction: Nursing theory constitutes a body of knowledge that supports nursing practice. It earns nursing a scientific development, help enhance the care nurses provide to clients and serves as basis for nursing practice.Purpose: The aim of this paper was to showcase the harmonisation of the nurses’ roles to clinical environment as a synergy to theory based nursing practice.Method: The position paper used theoretical and empirical evidences in drawing its stance through literature review. It addresses certain issues related to theory-based nursing practice. Result: The issues addressed by the paper includes: theory-practice artificial gap, research, evidence based practice, and nursing students learning in the application of nursing theories respectively. The paper revealed harmonisation of nurse academicians and practitioners roles to clinical environment as a solution.Conclusion: Nurses need to harmonise the roles of academicians and clinicians as a synergy that can yield a favourable outcome to nursing profession.